Phytoconstituents and Therapeutic Potential of Allium cepa Linn.– A Review - Bora, Kundan Singh; Sharma, Anupam (Pharmacognosy Reviews)
In the present scenario, herbal medicines have gained global importance with both medicinal and economic implications. Widespread use of herbs throughout the world has raised serious concerns over their quality, safety and efficacy. Thus, accurate scientific assessment has become a prerequisite for acceptance of health claims. Onion (Allium cepa Linn.), a member of the genus Allium, is the second most important horticulture crop all over the world. It is used as an important source of phytoconstituents and food flavour. Onions are one of the richest sources of flavonoids and organosulphur compounds. They possess a high level of antioxidant activity attributable to flavonoids quercetin, kaempferol, myricetin; pigments such as anthocyanins, and organonosulphur compounds. The most important among the sulphur compounds are the cysteine derivatives non-volatile Samino acids, S-alk(en)yl-substituted cysteine sulphoxides and their decomposition products such as thiosulfinates and polysulfides. These sulphure compounds and flavonoids possess antioxidant, antidiabetic, anti-inflammatory, anticancer, antimicrobial, antihyperlipidaemic, anticholesterolaemic, fibrinolytic, antiatherosclerotic, anticataractogenetic, antiplatelet aggregation, immunomodulatory, neuroprotective in ischemia and reperfusion-induced cerebral injury, and various other biological activities. Wide spectrum of biological activities makes A. cepa as potential therapeutic agent.
Keywords: Allium cepa; Anticancer; Antioxidant; Flavonoids; S-cysteine sulphoxides